BREEDING DOWNY MILDEW RESISTANT SORGHUM VARIETIES - K. H. ANAHOSUR, H. SHIVANNA AND (Indian Phytopathology, 2002)
Cross between susceptible high yielding variety (58-905) and resistant less yielding variety (0MRS-1) was effected and tested for resistance to downy mildew keeping high grain yield as primary requirement. F], F; and FI were tested and varieties 58-905 x DMRS-1-26, 58-905 x DMRS-1-27 and 58-905 x DMRS-1-29 with downy mildew resistance and high grain yield were developed.